Trastorno negativista desafiante y su influencia en los procesos cognitivos de un niño de 10 años - Donaire Solorzano, Katherine Graciela (2020)
In this case study the challenging negativist disorder and cognitive processes will be treated with the general objective of identifying whether this disorder influences the processes. To carry out the diagnosis, it was carried out through the application of psychometrics batteries that help to assess and give weight in the investigation such as Bender test, Staic test for Anxiety, EPQJ test to see the personality of the individual, followed by techniques such as the interview, semi-structured interview, clinic history.The most affected areas were cognitive and social-school behavior, causing the emotional area, thought and somatic area not to be reflected in a large percentage, but within the two areas mentioned above, a relationship is made with them in where it is evident that the one is causing the other area. A psychotherapeutic goal is established, after those goals were met there is an improvement in the child's behavior but in the child's cognitive processes such as memory, intelligence, language, perception, the response of improvement is slow being evidenced that the challenging negativist disorder It influences cognitive processes in a 10 year old child.